Lectures Versus Personalized Instruction: An Experimental Study in Elementary Managerial Accounting. - Bailes, Jack C. (The Accounting Review, 1979)
Abstract ABSTRACT: Few of the reported studies of innovative techniques for accounting education have found significant improvements in students' performance and attitude. This paper reports on an experimental study in an elementary managerial accounting class using an innovative teaching methodology, The Personalized System of Instruction (PSI). The PSI teaching method was selected for testing because studies in other academic disciplines had found that PSI classes performed better and had better attitudes than traditional lecture/discussion classes. The present study found significantly better performance and attitudes in PSI taught sections of an elementary managerial accounting class. The study also found a higher course drop-out rate for the PSI taught sections.